CNGC2 Is a Ca2+ Influx Channel That Prevents Accumulation of Apoplastic Ca2+ in the Leaf. Issue 2 (20th December 2016) - Wang, Yan; Kang, Yan; Ma, Chunli; Miao, Ruiying; Wu, Caili; Long, Yu; Ge, Ting; Wu, Zinian; Hou, Xiangyang; Zhang, Junxia; Qi, Zhi
Abstract : Arabidopsis CNGC2 is a Ca 2+ -permeable channel that mediates Ca 2+ influx into mesophyll cells near minor veins but has no direct role in the hypersensitive response or leaf senescence. Abstract: Ca 2+ is absorbed by roots and transported upward through the xylem to the apoplastic space of the leaf, after which it is deposited into the leaf cell. In Arabidopsis ( Arabidopsis thaliana ), the tonoplast-localized Ca 2+ /H + transporters CATION EXCHANGER1 (CAX1) and CAX3 sequester Ca 2+ from the cytosol into the vacuole, but it is not known what transporter mediates the initial Ca 2+ influx from the apoplast to the cytosol. Here, we report that Arabidopsis CYCLIC NUCLEOTIDE-GATED CHANNEL2 ( CNGC2 ) encodes a protein with Ca 2+ influx channel activity and is expressed in the leaf areas surrounding the free endings of minor veins, which is the primary site for Ca 2+ unloading from the vasculature and influx into leaf cells. Under hydroponic growth conditions, with 0.1 mm Ca 2+, both Arabidopsis cngc2 and cax1cax3 loss-of-function mutants grew normally. Increasing the Ca 2+ concentration to 10 mm induced H2 O2 accumulation, cell death, and leaf senescence and partially suppressed the hypersensitive response to avirulent pathogens in the mutants but not in the wild type. In vivo apoplastic Ca 2+ overaccumulation was found in the leaves of cngc2 and cax1cax 3 but not the wild type under the 10 mm Ca 2+ condition, as monitored by Oregon Green BAPTA 488 5N, a low-affinity and membrane-impermeable Ca 2+ probe. Our results indicate that CNGC2 likely has no direct roles in leaf development or the hypersensitive response but, instead, that CNGC2 could mediate Ca 2+ influx into leaf cells. Finally, the in vivo extracellular Ca 2+ imaging method developed in this study provides a new tool for investigating Ca 2+ dynamics in plant cells.